Removal of Ammonium Nitrogen from Petrochemical Wastewater by Anaerobic-Aerobic Process - Zhao, Qing; Chen, Xin; Tong, Ming; Zhao, Yin; Zhou, Yanbo; Lu, Jun (Asian Journal of Chemistry, 2013)
Pilot equipment was set up to evaluate effectiveness of anaerobic-aerobic (A/O) process on removing ammonia nitrogen (NH3-N) from petrochemical wastewater. The results showed that the anaerobic-aerobic process had a good biological degradation effect on NH3-N from petrochemical wastewater. Effluent NH3-N was below 2 mg/L during steady operation, which can meet the petrochemical wastewater discharge standards in China. The removal rate of NH3-N was nealy 100 % with the influent NH3-N from 20-105 mg/L. C/N ratio and pH value were the key factors on removal efficiency of nitrogen in the biosystem. The optimal experiment conditions were determined as follows: C/N ³ 5, pH value 7-8. The NH3-N biodegradation process can be described by Monod equation and the kinetics parameters were nmax = 0.12 h-1, KS = 7.22 mg/L.